John Updike and the Cold War : drawing the Iron Curtain - Miller, D. Quentin (Daniel Quentin), 1967- (University of Missouri Press, 2001)
"One of the most enduring and prolific American authors of the latter half of the twentieth century, John Updike has long been recognized by critics for his importance as a social commentator. Yet, John Updike and the Cold War is the first work to examine how Updike's views grew out of the defining context of American culture in his time - the Cold War. Quentin Miller argues that because Updike's career began as the Cold War was taking shape in the mid-1950s, the world he creates in his entire literary oeuvre - fiction, poetry, and nonfiction prose - reflects the optimism and the anxiety of that decade."--Jacket